2017
DOI: 10.4067/s0718-95162017000400002
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds stimulate plant growing and seed germination of Lactuca sativa

Abstract: Volatile organic compounds (VOCs) emitted by Bacillus species have been reported as growth inducers in Arabidopsis thaliana, but their effects on horticultural species have been scarcely studied. In this study, Lactuca had a greater effect. It noteworthy that root development was higher when BCT9 was grown in MRVP-A than in the others culture medium. The identified VOCs released by BCT9 in MRVP-A were 3-hydroxy-2-butanone, 2,3-butanediol, 2-nonanone, 2-undecanone, 2-tridecanone and 2-pentadecanone. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Pseudomonas brassicacearum and Pseudomonas putida for example, release long-chain hydrocarbons like triacontane (C 30 H 62 ), octacosane (C 28 H 58 ), heptacosane (C 27 H 56 ), and heneicosane (C 21 H 44 ) with molecular weight as high as 422 g/mol and vapor pressure as low as 3.6 × 10 −12 kPa and still being detected in the headspace of agar slant tubes by solid-phase micro-extraction (SPME) method (Giorgio et al, 2015). So, finding long-chain alkanes in our results was not surprising since the quantity and identity of volatile blends produced by rhizobacteria vary significantly among species (Ryu et al, 2003;Lee et al, 2012;Farag et al, 2013;Fincheira et al, 2017;Giorgio et al, 2015). The release of long-chain alkanes (C31, C28, C27, and C21) by rhizobacteria isolated from common bean was previously reported (Giorgio et al, 2015), but the biological role of long-chain alkanes was not further assessed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Pseudomonas brassicacearum and Pseudomonas putida for example, release long-chain hydrocarbons like triacontane (C 30 H 62 ), octacosane (C 28 H 58 ), heptacosane (C 27 H 56 ), and heneicosane (C 21 H 44 ) with molecular weight as high as 422 g/mol and vapor pressure as low as 3.6 × 10 −12 kPa and still being detected in the headspace of agar slant tubes by solid-phase micro-extraction (SPME) method (Giorgio et al, 2015). So, finding long-chain alkanes in our results was not surprising since the quantity and identity of volatile blends produced by rhizobacteria vary significantly among species (Ryu et al, 2003;Lee et al, 2012;Farag et al, 2013;Fincheira et al, 2017;Giorgio et al, 2015). The release of long-chain alkanes (C31, C28, C27, and C21) by rhizobacteria isolated from common bean was previously reported (Giorgio et al, 2015), but the biological role of long-chain alkanes was not further assessed.…”
Section: Discussionmentioning
confidence: 57%
“…that can stimulate plant growth, control plant pathogens, and induce systemic disease resistance (Ryu et al, 2003;Audrain et al, 2015;Fincheira et al, 2017). Different environmental signals can induce or preclude seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…For example, certain strains of PGPR, when seeds are dressed or primed, or inoculated in the soil, are found to substantially improve seed germination and seedling growth of various crop species including radish [ 29 ], sunflower [ 30 ], chickpea [ 31 ], maize [ 32 ] and rice [ 33 ]. In addition to microbial strains, microbe-based compounds, for instance signals [ 34 , 35 , 36 , 37 ] and other VOCs (volatile organic compounds) [ 38 , 39 , 40 ], have been found to have stimulatory seed germination effects. In this part of the research, CFS prepared from cultures of a novel bacterial strain Devosia sp.…”
Section: Discussionmentioning
confidence: 99%
“…An important component of this plasticity is accelerated seedling emergence in competitive neighborhoods ( Sales, Pérez-García & Silveira, 2013 ; Tielbörger & Prasse, 2009 ; Verdú & Traveset, 2005 ). The potential mechanisms of seed germination plastically responding to neighbors may be attributed to the fact that germinating seeds may emit volatile organic compounds (VOCs) based on the growing conditions ( Fincheira, Parada & Quiroz, 2017 ; Motsa et al, 2017 ). Studies showed that temperature level affects production rates of VOCs and may change the volatile composition via affecting enzyme activity that degrades the storage reserves in the seeds; hence affects breaking seed dormancy ( Effah, Holopainen & McCormick, 2019 ; Motsa et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%